IFT46 gene promoter-driven ciliopathy disease model in zebrafish - Lee, Mi-Sun; Han, Hye-Jeong; Choi, Tae-Ik; Lee, Kang-Han; Baasankhuu, Amartuvshin; Kim, Hyun-Taek; Kim, Cheol-Hee (Frontiers in Cell and Developmental Biology, 2023)
Ciliopathies are human genetic disorders caused by abnormal formation and dysfunction of cellular cilia. Cilia are microtubule-based organelles which project into the extracellular space and transduce molecular and chemical signals from the extracellular environment or neighboring cells. Intraflagellar transport (IFT) proteins are required for assembly and maintenance of cilia by transporting proteins along the axoneme which consists of complex A and B. Ift46, a core IFT-B protein complex is required for cilia formation and maintenance during vertebrate embryonic development. Here, we introduce transgenic zebrafish lines under control of ciliated cell-specific ift46 promoter to recapitulate human ciliopathy-like phenotypes. We generated a Tg(ift46:GAL4-VP16) line to temporo-spatially control expression of effectors including fluorescent reporters or nitroreductase based on the GAL4/UAS system, which expresses GAL4-VP16 chimeric transcription factors in most ciliated tissues during embryonic development. To analyze the function of ift46-expressing ciliated cells during zebrafish development, we generated the Tg(ift46:Gal4-VP16;UAS;nfsb-mCherry) line, a ciliated cell-specific injury model induced by nitroreductase (NTR)/metrodinazole (MTZ). Conditionally controlled ablation of ciliated cells in transgenic animals exhibited ciliopathy-like phenotypes including cystic kidney, pericardial and periorbital edema. Altogether, we established a zebrafish NTR/MTZ-mediated ciliated cell injury model, which recapitulates ciliopathy-like phenotypes and may be a vertebrate animal model to further investigate the etiology and therapeutic approaches to human ciliopathies.